CERMIN EDUKASI MENINGKATKAN PENGETAHUAN DAN SIKAP HIGIENE PERSONAL PENJAMAH MAKANAN - Putri Ronitawati; Nadina Karima; Vitria Melani; Mertien Sa'pang; Rachmanida Nuzrina (Poltekkes Kemenkes Semarang, 2021)
Background: Personal hygiene is the basic principle of foodservice. Poor personal hygiene practices can lead to increase risk of microbial contamination in food. The personal hygiene of Islamic boarding schools’ food handlers are still low related to lack of knowledge. It caused by various factors, such as knowledge, attitudes, education, length of work, and habits on processing foodObjective: To examine the effect of mirroring education on the personal hygiene’s knowledge and attitudes of Islamic boarding school food handlers’ in Jombang.Methods: A pre-experimental study with a pretest-posttest group design. Total sampling were 41 food handlers in Islamic boarding school in Jombang. Data were analyzed by Paired Sample T-test and Wilcoxon test.Results: The age distribution of the respondents were 2,4% as the oldest age (58 years old) and 7,3% as the youngest age (17 years old), 26 respondents (63,4%) had working period 4 years and 22 people (53,7%) with low education. Knowledge and attitude about personal hygiene before and after education were significantly different (p=0, 01), also There were differences in knowledge and attitude about personal hygiene before and one week after education (p=0,01).Conclusion: Mirroring education can improve personal hygiene’s knowledge and attitudes of food handlers.